Nano Tips to Stop Overthinking with Shadé Zahrai. - Zahrai, Shadé (linkedin.com, 2022)
Get tips to stop overthinking your career path, relationships, and goals. Each video is less than two minutes long, so you can make learning fit into even your busiest days.